2016
DOI: 10.3389/fnhum.2016.00254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gene × Attachment Interaction on Adolescents’ Emotion Regulation and Aggressive Hostile Behavior Towards their Mothers during a Computer Game

Abstract: Adolescence is a time of increased emotionality and major changes in emotion regulation often elicited in autonomy-relevant situations. Both genetic as well as social factors may lead to inter-individual differences in emotional processes in adolescence. We investigated whether both 5-HTTLPR and attachment security influence adolescents’ observed emotionality, emotional dysregulation, and their aggressive hostile autonomy while interacting with their mothers. Eighty-eight adolescents at age 12 were observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Certain caregiving qualities that may be important for the promotion of attachment security in adolescence, which might include parental monitoring and child self‐disclosure that facilitates parental monitoring (Branstetter, Furman, & Cottrell, ; Kerns, Aspelmeier, Gentzler, & Grabill, ; Kerr & Stattin, ), are not detectable from caregiving assessments in early childhood. Additionally, the ‘state of mind’ assessment, which is the basis for categorizing adolescents as displaying a Secure or Insecure attachment in much of the literature, may reflect not so much prior or current caregiving qualities as much as a broader construct of emotion regulation that integrates caregiving and other experiences and reflects a broad‐based measure of psychological well‐being (Allen & Manning, ; Allen & Miga, ; Zimmermann & Spangler, ). Perhaps related to these findings is the evidence that individual differences in attachment security appear to be much more strongly influenced by genetic factors in older than younger children (Fearon, Shmueli‐Goetz, Viding, Fonagy, & Plomin, ; O'Connor & Croft, ).…”
Section: Introductionmentioning
confidence: 99%
“…Certain caregiving qualities that may be important for the promotion of attachment security in adolescence, which might include parental monitoring and child self‐disclosure that facilitates parental monitoring (Branstetter, Furman, & Cottrell, ; Kerns, Aspelmeier, Gentzler, & Grabill, ; Kerr & Stattin, ), are not detectable from caregiving assessments in early childhood. Additionally, the ‘state of mind’ assessment, which is the basis for categorizing adolescents as displaying a Secure or Insecure attachment in much of the literature, may reflect not so much prior or current caregiving qualities as much as a broader construct of emotion regulation that integrates caregiving and other experiences and reflects a broad‐based measure of psychological well‐being (Allen & Manning, ; Allen & Miga, ; Zimmermann & Spangler, ). Perhaps related to these findings is the evidence that individual differences in attachment security appear to be much more strongly influenced by genetic factors in older than younger children (Fearon, Shmueli‐Goetz, Viding, Fonagy, & Plomin, ; O'Connor & Croft, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, parental sensitivity and parental intrusiveness may differentially influence the intercept and slope of self-control development (Geeraerts et al, 2021 ). For other genetic predispositions and also for other developmental outcomes besides self-regulation, specific aspects of sensitivity or caregiving by both mothers and fathers or attachment security may well play an important role (Spangler et al, 2009 ; Zimmermann et al, 2009 ; Davies et al, 2015 ; Zimmermann and Spangler, 2016 ; Baptista et al, 2017 ; Neppl et al, 2020 ; Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This in turn generalizes to other interpersonal relationships, with aforementioned positive effects on adjustment (e.g., Cassidy & Shaver, 2008). Although early behavioral genetics studies suggested limited if any heritable component of attachment security or disorganization (Bokhorst et al., 2003), recent molecular genetics studies show moderation of (a) stability in attachment security from childhood to late adolescence (e.g., Raby et al., 2015), (b) genetic susceptibility of children to sensitive caregiving (e.g., Gervai, 2009), and (c) interactions between adolescents’ attachment security and serotonin transporter alleles in predicting dysregulated emotion expressed toward mothers (Zimmermann & Spangler, 2016). To date, however, limited research addresses genetic moderation of longitudinal associations between early child attachment security and later positive socioemotional outcomes.…”
Section: Introductionmentioning
confidence: 99%